SIKAP PEGAWAI RRI BENGKULU TENTANG TAYANGAN TALKSHOW MARIO TEGUH GOLDEN WAYS DI METRO TV SEBAGAI MOTIVASI KERJA - Jusarman Sanusi; Yusuarsono -; Sri Narti (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
The purpose of this study was to determine the attitude of Indonesia Republic Radio employees Bengkulu after watching Mario Gonden Waystalkshow on Metro TV as motivation to work.Data analysis technique used is descriptive qualitative method.Data were collectedby using observation, interviews and documentationtechniques.This study uses five informants, they weretwo staffs, one announcer and two journalists of Indonesia Republic RadioBengkulu.This study presented data based on interviews, observation and documentation in the form of words.Analyses were performed by using the S-O-R theorythat is Stimulus, Organism and Response.Based on this research, it found that employees of RRI Bengkulu likedthe impressions of the talkshow for it’s considered capable of providing good information and motivation to work.Meanwhile, if it seen from the attitude changes, therewere changes in employee attitudes after watching Mario Teguh Golden Ways on Metro TV.Changes in attitude toward a better than ever, especially in terms of work, the employee of Radio Republic Indonesia Bengkulu feel motivated to work harder to reach the ideals to be expected during this time. This event was considered to have helped to generate employment for employee motivationin Radio Republic Indonesia Bengkulu.